PARAMETER GENETIK DAN KORELASI KARAKTER AGRONOMI KACANG PANJANG POPULASI F4 PERSILANGAN TESTA COKLAT X COKLAT PUTIH - Sa?diyah, Nyimas; Basoeki, Tjipto Roso (JURNAL AGROTROPIKA, 2010)
This study estimated Genetic Parameters and Correlation Among Agronomic Characters of Yard-Long Bean. Research was conducted in the Experiment Station of Politeknik Negeri Lampung, Bandar Lampung, from March to July 2009. The genotypes evaluated was the F4 population derived from crosses between the lines of testa coklat (brown) x coklat putih (white-Brown). Variables observed were the flowering date, the harvesting date of young pods, the average pod length per plants, the numbers of mature pod per plants, average number of lokul per pod, seed number per plant, weight of 100 seeds, and average number of seeds per plants. Except the number of flower per stem, the estimates of genetic variances, phenotypic variences, and heritability were hight for all variables observed. The estimates of the parameters for the number of flower per stem was narrow/low, except the flowerity date, harvesting date, pod lenght, and number of lokuls. All variables were significantly correlated with.Key words: genetic parameters, correlation, long beans